2014
DOI: 10.1080/01652176.2014.979512
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum neutralization and enzyme-linked immunosorbent assay on sera from porcine epidemic diarrhea virus vaccinated pigs

Abstract: Background: Porcine epidemic diarrhea virus (PEDV) is an economically important pathogen of swine. Objective: Serum neutralization (SN) and enzyme-linked immunosorbent assay (ELISA) test results as well as the utility of spike proteins S1, S2, and S3 and entire nucleocapsid protein were compared. Animals and methods: Serum samples from 400 pigs vaccinated against PEDV strain SM98P were collected from 78 farms in Korea. SN test and ELISA were performed to confirm the presence of antibodies. For prokaryotic expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…Additionally, levels of NA were more closely correlated with IgA than IgG (Fig. 3B-D), as seen in other studies (Paudel et al, 2014). Abundant anti-PEDV NA have been demonstrated in colostrum on the day of birth, decreasing rapidly in milk by day 3, and gradually declining further from days 3-19 post-farrowing, which may contribute to variable protective capacity .…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, levels of NA were more closely correlated with IgA than IgG (Fig. 3B-D), as seen in other studies (Paudel et al, 2014). Abundant anti-PEDV NA have been demonstrated in colostrum on the day of birth, decreasing rapidly in milk by day 3, and gradually declining further from days 3-19 post-farrowing, which may contribute to variable protective capacity .…”
Section: Discussionsupporting
confidence: 83%
“…The S1-part of the spike protein is the most variable part between related coronaviruses and there is no cross reactivity with other coronaviruses such as Transmissible gastroenteritis coronavirus (TGEV), Porcine respiratory coronavirus (PRCoV) and Porcine Delta Coronavirus (PDCoV) as previously described (Gimenez-Lirola et al, 2017;Lin et al, 2015b). Because results of immunoassays based on the S protein correlate well with viral neutralization (Paudel et al, 2014), as shown in Supplementary Table 1, we decided to use the VNT as an alternative sero-diagnostic assay.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant porcine enteric coronavirus between TGEV and PEDV is in brown. Because viral neutralizing epitopes are located on the S protein, the results of PEDV S protein-based immunoassays correlated well with viral neutralization (VN) titers (Paudel et al, 2014), which is important for clinical protection. In addition, antibodies against the S protein remained detectable for longer periods of time than antibodies to the N protein in the sera of PEDV-infected pigs (Knuchel et al, 1992).…”
Section: Antigenic Relationships Between Pedv and Other Alphacoronavimentioning
confidence: 97%
“…Truncation of the antigenic site in the N-terminal region could help exclude the possible serological cross-reactivity and enhance the sensitivity/specificity of the immunoassays. Alternatively, PEDV membrane (M) and S proteins could serve as specific antigens for immunoassays (Fan et al, 2015;Gerber et al, 2014;Knuchel et al, 1992;Paudel et al, 2014).…”
Section: Antigenic Relationships Between Pedv and Other Alphacoronavimentioning
confidence: 99%